Measuring forgiveness: psychometric properties of a new culturally sensitive questionnaire: the Bolton Forgiveness Scale (BFS) - Amanze, Reginald U. (Mental health, religion & culture, 2019)
Forgiveness is a universal construct. A forgiveness measure should ensure good and diverse cultural representation and inclusivity in its development, validation and usage. The 15-item Bolton Forgiveness Scale (BFS) assesses dispositional forgiveness. Items came from interviews with 53 Nigerian and British people, existing scales and the research literature. Exploratory factor analysis with a student sample (n = 733) was followed by confirmatory factor analysis with a general sample (n = 2,017). This indicated a robust three-factor structure. Factors were, coming to terms and letting go (CLTG), developing positive feelings (DPF) and giving benefit of the doubt (GBD). Scale Validity was established and a new forgiveness definition emerged as a process that involves developing and strengthening the capacity to give benefit of the doubt that enables the offended come to terms with and let go of hurt with its negative affect thereby giving way gradually to positive feelings towards the transgressor.